Introdução ao cultivo in vitro de açoita-cavalo (Luehea divaricata Martius et Zuccarini) - Flôres, Andressa Vasconcelos (2007)
Açoita-cavalo , Luehea divaricata Martius et Zuccarini, pertaining to the Tiliaceae family, is a forest species that suffered great entropic action in the last decades, fact that contributed a lot to the reduction of the natural populations, becoming necessary the conservation of germ plasma in vitro. It presents slow and irregular, changeable germination between 20% and 75%, and viability of the seeds very unevenness. These characteristics contribute for one reduced frequency of the species in natural forests. As form of vegetative propagation, the micropropagation becomes an alternative for the regeneration of plants that present difficulty of natural reproduction, beyond presenting itself as a conservation way for the species. The work had as objective to establish a protocol of disinfestations for aseptic germination of açoita-cavalo seeds, to determine the more efficient type of explants and way of culture for the establishment in vitro, to verify the influence of the orientation of the explants in the bottle on the development in vitro and to observe the influence of different concentrations of cytokine BAP in the multiplication of nodes segments of açoita-cavalo . The works had been carried through in the Laboratory of Tissue Culture of the Núcleo de Biotecnologia e Melhoramento, Departamento de Fitotecnia, Centro de Ciências Rurais, Universidade Federal de Santa Maria, in Santa Maria, RS. The seeds had been collected and conserved by Fundação Estadual de Pesquisa Agropecuária - Fepagro/Florestas in Santa Maria, RS, in 2004 and 2005, and seedlings gotten in had been used as source of explants for the studies vitro. During the disinfestations experiments it was observed that the immersion of the seeds in hot water is basic for the control (partial) of microorganisms associated to the seeds, as well as promoting a bigger tax of germination. The mercury chloride controlled the fungal contamination partially and total the bacterial contamination, however it demonstrated toxicity to the development of seedling with the yellowish leaf appearance. For the establishment in vitro of açoita-cavalo can be used as many apexes shoot as nodes segments, independent of the way of culture WPM or MS. For the rooting, the half WPM was more efficient, in the two types of node explants, apexes shoot and segments. Aiming at to maximize the açoita-cavalo culture, the half WPM must be used for the establishment, for having reduced cost and explants of the type nodal segment, that are produced in bigger number for seedling. In does not have influence of the orientation of the explants in relation to the bottle in the development of cultures vitro of açoita-cavalo . In the tested concentrations, cytokine BAP inhibited the formation of shoot and leaves. The tested concentrations of BAP had been high and can have been toxic to the development of the node segments of açoita-cavalo . New studies must more be carried through for an ascertainment deepened of the culture in vitro of açoita-cavalo .